2001
DOI: 10.1046/j.1464-5491.2001.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the use of dietetic services by patients with diabetes mellitus

Abstract: This study confirmed that many patients with diabetes do not make use of professional dietetic services, and has highlighted some of the routinely documented characteristics that are associated with use of dietetic services. There appears to be scope to improve uptake of dietetic services by patients with diabetes, and to investigate further individual factors that affect access and attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…These results were in accordance with studies in other healthcare professions [18,31,32]. However, the positive association between patients’ age and a lower number of consultations per treatment was not in accordance with other studies [18,29].…”
Section: Discussionsupporting
confidence: 76%
“…These results were in accordance with studies in other healthcare professions [18,31,32]. However, the positive association between patients’ age and a lower number of consultations per treatment was not in accordance with other studies [18,29].…”
Section: Discussionsupporting
confidence: 76%
“…Panser et al found that age modified by the effect of gender was the strongest risk factor for hospitalisation in patients with type 2 diabetes, while the presence of complications such as coronary heart disease, retinopathy and persistent proteinuria were also significant risk factors [20]. The use of dietetic services is related to gender, disease duration and the use of insulin [21]. Another study showed that nearly one third of the diabetic patients had never visited an ophthalmologist [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many people with diabetes have never had a consultation with a dietitian. In a study from Sunderland, only 59% of patients had seen a dietitian in the previous eight years, and many patients with impaired renal function or with dyslipidaemia had never seen a dietitian 2. Similarly, in a questionnaire survey of people with diabetes in Herefordshire, only 75% could recall ever having seen a dietitian and, of these, 44% had seen a dietitian only once and a further 18% saw a dietitian only ‘rarely or irregularly’ 3…”
Section: Discussionmentioning
confidence: 99%
“…This evidence of a considerable un‐met need, as perceived by people with diabetes, is unsatisfactory in what should be a patient‐centred service, and particularly so because there is evidence, which has been reviewed in two recent publications,2, 4 that contact with a professional dietitian is clinically effective and also cost effective. In contrast, there is no published evidence for the effectiveness of dietary advice given to people with diabetes by other health professionals, although in a randomised trial of the dietary management of hypercholesterolaemia (in which the dietary advice is very similar to that required by most people with type 2 diabetes), counselling by dietitians achieved greater reductions in LDL cholesterol than did that given by doctors 5…”
Section: Discussionmentioning
confidence: 99%